STUDENTS' ENGLISH INTONATION ABILITY IN USE: A STUDY OF FOURTH SEMESTER ENGLISH DEPARTMENT STUDENTS AT IAIN PAREPARE - Basmala Basmala; Abdul Haris Sunubi; Kalsum Kalsum (STKIP Darud Da'wah Wal Irsyad Pinrang, 2025)
This study examines the proficiency level of fourth-semester EFL students at IAIN Parepare regarding their application of English intonation patterns. Intonation serves as a crucial element within pronunciation that significantly influences meaning conveyance and emotional expression during verbal communication. The research employed a quantitative descriptive approach involving twenty student participants. Data collection utilized two assessment instruments: a multiple-choice examination and voice recording tasks, each containing ten items focused on ascending and descending intonation patterns. Research findings indicate that students demonstrate